The Effect of E-Commerce, Price and Service Quality on Consumer Interest in PT Jalur Nugraha Ekakurir (JNE) - Inggrid; Kristi Endah Ndilosa Ginting; Sandy Gozali; Sinta Teresia; Kelvin Khusuma (Jurnal Mantik, 2021)
This study aims to test and analyze the effect of E-Commerce, Price and Service Quality on Consumer Interest in PT Nugraha Ekakurir Line (JNE).The research method uses quantitative. The population was 196 consumers and the sample was 132 consumers. The sampling technique used was random sampling.The results of the calculation of hypothesis testing partially and Simultaneously E-Commerce, Price and Service Quality have a positive and significant effect on the Purchase Intention of Medan-Jakarta Delivery at PT Nugraha Ekakurir (JNE) Line. HThe result of the coefficient of determination test is the Adjusted R Square value of 0.216, this means 21.6% of the variation of the Purchase Interest variable. which can be explained by the variation of the independent variables, namely E-commerce, Price and Service Quality, while the remaining 78.4% is explained by other variables not examined in this study, such as innovation, level of trust, promotion and development and so on.